Application of Fourier transform infrared spectroscopy for the quality and safety analysis of fats and oils: A review. Issue 22 (16th December 2019) - Li, Qi; Chen, Jia; Huyan, Zongyao; Kou, Yuxing; Xu, Lirong; Yu, Xiuzhu; Gao, Jin-Ming
Abstract: Fats and oils are essential food components. Their quality and safety pose major concerns for consumers and food producers because of factors such as oxidation and rancidity, excessive levels of trans fatty acid (TFA), and widespread adulteration. Thus, a rapid and easy-to-use technique must be exploited for quality parameter evaluation and monitoring to ensure the edibility, safety, and quality of fats and oils. In the last decades, Fourier transform infrared (FTIR) spectroscopy has shown great potential in analyzing fats and oils given its speed and simplicity. FTIR-based analytical techniques for common intrinsic quality parameters, including peroxide value, free fatty acid, moisture, TFA, iodine value, as well as oxidation stability, adulteration, and classification of various fats and oils, are summarized in this review. The advantages and disadvantages of selected infrared spectral accessories and sample preparation and spectral processing methods are highlighted. The prospects and reformative aspects for future application of the FTIR technique in the field of fats and oils are also discussed. This review may serve as a basis for applying FTIR not only in future research but also in the fat and oil industries.